COMMUNICATION FOR THE 21ST CENTURY: BLOGS AND SOCIAL NETWORKS - ALCNAUER, Július (Trends in education, 2010)
The paper presents new directions in communication in the 21st century and their influence on the public opinion. Also it presents a survey of students´ opinions and the change in the attitude of companies in the formation of public relations. It suggests a possibility of conducting independent research into the blog efficiency using the EIZ method in school practice.
Keywords: Blog; Social Networks; EIZ.